Transport model calculations of deuteron production in relativistic hadron and heavy‐ion collisions. Issue 9 (8th January 2020) - Bleicher, Marcus; Hillmann, Paula; Reichert, Tom; Steinheimer, Jan; Sombun, Sukanya; Herold, Christoph; Limphirat, Ayut; Yan, Yupeng
Abstract: The production of deuterons and heavy clusters such as triton and helium (or even hypertriton) has gained increased attention during the last years. This attention was mainly stimulated by the recent hypertriton data and has led to the question of whether cluster production is driven by coalescence of its constituents or by thermal emission of the cluster itself. Here, we explore the cluster production by coalescence using the Ultra‐relativistic Quantum Molecular Dynamics model and a phase–space coalescence model. We explore deuteron production over a wide range of reactions and energies from s NN = 2 GeV to s NN = 2 TeV. Overall, we observe that coalescence leads to an excellent description of the deuteron yields and momentum distributions.